PROBLEMS OF POLISH CITIES. THE INFLUENCE OF SUBURBANIZATION PROCESSES ON SHAPING SPATIAL STRUCTURE - Zabawa-Krzypkowska, Joanna (European Scientific Journal, ESJ, 2014)
The paper presents processes which have been taking place in Polish cities since the time of the political transformation in 1989. It shows changes in spatial and social composition which have impact on the life and dwelling quality in a city. It ponders on problems of suburbanization, disappearing city centres and public spaces as well as social stratification.